A STUDY OF THE IMPACT OF THE COVID-19 PANDEMIC MATERNAL AND CHILD HEALTH SERVICES (MCH) - Lailiyah, Siti Rochimatul; Daniyanti, Eka Suci (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
The Maternal and Child Health Program (MCH) is one of the main priorities for health development in Indonesia. The problem in this study is the decline in visits to several indicators of MCH services, namely K1, K4, Pn, Kf, KN and Kn Complete percentage decrease about 35% -10% on each indicator during the COVID-19 pandemic in 2019, 2020, and 2021 as of May. The purpose of the study was to examine the impact of Maternal and Child Health Services (KIA) during the Covid19 pandemic at the Polindes, Pocong Tragah Village, Bangkalan Regency. This study used a descriptive method, the variables in this study were MCH services using PWS MCH (K1, K4, Pn, Kf, Kn1, Kn and Kn Complete). The research population was visiting K1, K4, Pn, Kf, and Kn in 2019, 2020, and 2021 as of May. The type of data collection included the type of survey research. And based on the source of this research data, including secondary research with Univarial data analysis The results showed that in 2019-2020 there was a decrease in visits to K1 34%, K4 29%, Pn 18%, Kf 34%, Kn 10% and Kn Complete 30%. In 2020-2021 as of May, there was an increase in K1 visits by 19%, K4 12%, Kn 18%, Kf 34%, Pn visits a 5% decline and Kn Complete 37% at. From the analysis carried out, there was a decrease in visits in 2019-2020, among others, due to anxiety, lack of knowledge, the emergence of the COVID-19 pandemic, and changed in visits. In 2020-2021 as of May, there was an increase. It is hoped that midwives will try to make certain strategies so that MCH services continue to run as targeted by the government..